DEVELOPMENT AND VALIDATION OF A HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHY FOR THE DETERMINATION OF TERBUTALINE SULFATE, BROMHEXINE HYDROCHLORIDE, AND ETOPHYLLINE IN PHARMACEUTICAL DOSAGE FORM - MEHUL M PATEL,; JIGISHA CHAUHAN,; HARSHAL SHAH, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The study aimed to development and validation of simple, precise, and reliable high-performance thin-layer chromatography (HPTLC) for the determination of terbutaline sulfate (TBS), bromhexine hydrochloride (BRH), and etophylline (ETP) in pharmaceutical dosage form. Methods: A simple, precise, rapid, and accurate HPTLC method was developed for the estimation of TBS, BRH, and ETP in pharmaceutical dosage form. Pre-coated silica gel G60 F254 aluminum sheet (10 cm2×10 cm2 and thickness 0.2 mm) was used as stationary phase while mobile phase consisting of benzene: methanol:glacial acetic acid 8:0.5:1.5 v/v/v detection at 275 nm. The present method had validated according to ICH guidelines. Results: Migration distance found 80 mm at 275 nm. The retention factor found to be 0.24, 0.57, and 0.68, respectively. The detector response was linear in the concentration range of 60–210 ng/band, 2400–8400 ng/band, and 96–336 ng/band, respectively. The linear regression equation being Y=32.20x−562.9, Y=11.79x−1711, and Y=1.756x−5636, respectively. The limit of detection for TBS 0.677 μg, for BRH 8.123 μg, and for ETP 57.915 μg and limit of quantification to be 2.053, 24.617, and 175.5 μg, respectively, were found. The developed method validated by ICH guideline, i.e., accuracy, precision, robustness, specificity, and system suitability. Conclusion: In this study, we had developed a simple, fast, and reliable HPTLC method for the determination of TBS, BRH, and ETP in pharmaceutical dosage form.